A STUDY ON THE PROBLEMS AND COUNTERMEASURES OF ENDOGENOUS CAPACITY OF FEMALE ECOLOGICAL MIGRANTS IN GUIZHOU PROVINCE, CHINA - Wenjie Yang; Clinton Chidiebere Anyanwu (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2025)
This study explores the endogenous development capacity of female ecological migrants in Guizhou Province, China. Using a quantitative survey of 945 female migrants, the research investigates the challenges in economic production, social participation, psychological adjustment, and household management. Results reveal that although these women possess strong ecological awareness and safety knowledge, they face significant limitations in production capacity, especially in agricultural production and entrepreneurial skills. Age and educational attainment are critical influencing factors; older women and those with lower educational attainment demonstrate weaker adaptive abilities. The study proposes a "problem-education-application" model and recommends vocational training, community-based education programs, and the creation of flexible employment opportunities. This research contributes to sustainable development discourse by providing practical policy recommendations to empower female ecological migrants and improve their quality of life in resettlement areas. Findings offer practical guidance for gender-sensitive ecological resettlement policies and sustainable capacity-building programs.